Bereavement rituals and their related psychosocial functions in a Northern Sotho community of South Africa. Issue 2 (7th February 2021) - Makgahlela, Mpsanyana; Sodi, Tholene; Nkoana, Shai; Mokwena, Jabu
Abstract: The study sought to explore bereavement rituals and their related psychosocial significance in an African cultural setting. A descriptive phenomenological design was adopted. Fourteen adults were purposefully sampled to participate in in-depth interviews. Data were analyzed using Hycner's adapted phenomenological method, which resulted in four themes: (a) the cleansing ritual ceremony/ go-ntšha setšhila, (b) ancestor reverence rituals, (c) rituals for protecting the deceased spirit, and (d) vengeance ritual/ letswa . Ritual performance is associated with diverse psychosocial benefits including the prevention of a culture-specific bereavement illness. Essentially, ritual performance is for healing in that it lessens bereavement from becoming disabling.